2013
DOI: 10.1056/nejmoa1214091
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Metabolism in the Li–Fraumeni Syndrome

Abstract: SUMMARY There is growing evidence that alterations in metabolism may contribute to tumorigenesis. Here, we report on members of families with the Li–Fraumeni syndrome who carry germline mutations in TP53, the gene encoding the tumor-suppressor protein p53. As compared with family members who are not carriers and with healthy volunteers, family members with these mutations have increased oxidative phosphorylation of skeletal muscle. Basic experimental studies of tissue samples from patients with the Li–Fraumeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 24 publications
8
98
1
Order By: Relevance
“…We previously reported that LFS family members who carried TP53 mutations have increased oxidative metabolism (7). These findings were confirmed in a mouse model of LFS that demonstrated the distinction between p53 null and p53 mutant states in regulating the mitochondria (8,9).…”
Section: Introductionmentioning
confidence: 55%
“…We previously reported that LFS family members who carried TP53 mutations have increased oxidative metabolism (7). These findings were confirmed in a mouse model of LFS that demonstrated the distinction between p53 null and p53 mutant states in regulating the mitochondria (8,9).…”
Section: Introductionmentioning
confidence: 55%
“…Compromised exercise capacity in p53-null mice and the effect of mutated p53 on skeletal muscle oxidative metabolism in a human translational study have underscored the importance of this tumor suppressor in exercise physiology (13,17,18,24). A number of studies have explored the effects of exercise on p53.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 also directly stimulates mitochondrial oxidative phosphorylation through transcriptional activation of the gene-encoding synthesis of cytochrome c oxidase 2 (Sco2) (Matoba et al 2006). Interestingly, dysregulated oxidative phosphorylation has been observed in cells from patients with Li -Fraumeni syndrome, which is attributed partly to altered Sco-2 expression (Wang et al 2013).…”
Section: Tumor-suppressor Functions Of Tp53 Pathwaymentioning
confidence: 99%